2020
DOI: 10.18632/aging.102683
|View full text |Cite
|
Sign up to set email alerts
|

DNAH10 mutation correlates with cisplatin sensitivity and tumor mutation burden in small-cell lung cancer

Abstract: Chemotherapies based on platinum have been the standard first-line treatment for patients with small-cell lung cancer(SCLC) in the past years. However, the progression of patients occurs mostly due to rapid development of resistance to chemotherapy. In addition, the mechanisms involved in development of cisplatin-resistance in SCLC remain undetermined. Here, we analyzed whole-exome sequencing(WES) datasets from Genomics of Drug Sensitivity in Cancer(GDSC, N=55) and WES data and overall survival(OS) from a publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…In addition, our previous study demonstrated that cancer cells with high TMB are associated with higher IC50 values (21), which is consistent with our current conclusion, suggesting that high TMB may also be a mechanism of cisplatin resistance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, our previous study demonstrated that cancer cells with high TMB are associated with higher IC50 values (21), which is consistent with our current conclusion, suggesting that high TMB may also be a mechanism of cisplatin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…ERBB amplification (18), oncogene EGFR (19) and FLT3 mutations (20) are also sensitive to their target inhibitors. Recent studies have found that new gene mutations are associated with chemotherapy sensitivity and patient prognosis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The distributions of the risk score, survival time, and expression profiles were shown in Additional file 3 : Figure S2Aā€“C. Overall tumor mutation burden (TMB) reflects the number of mutations in tumor cells and is a quantifiable biomarker [ 24 ]. We have calculated the TMB of the melanoma genome and explored the correlation between risk score and TMB (Additional file 3 : Figure S2D).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on CDDP resistance have mainly focus on drug accumulation, DNA damage repair, key signaling pathways and the tumor microenvironment (TME) (Chen and Chang, 2019). In addition, cancer stem cells play an important role in CDDP resistance and tumor progression (Li et al, 2020;Qiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%